Exteroceptive and Interoceptive Body-Self Awareness in Fibromyalgia Patients - Valenzuela-Moguillansky, Camila; Reyes-Reyes, Alejandro; Gaete, María I. (Frontiers in Human Neuroscience, 2017)
Fibromyalgia is a widespread chronic pain disease characterized by generalized musculoskeletal pain and fatigue. It substantially affects patients’ relationship with their bodies and quality of life, but few studies have investigated the relationship between pain and body awareness in fibromyalgia. We examined exteroceptive and interoceptive aspects of body awareness in 30 women with fibromyalgia and 29 control participants. Exteroceptive body awareness was assessed by a body-scaled action-anticipation task in which participants estimated whether they could pass through apertures of different widths. Interoceptive sensitivity (IS) was assessed by a heartbeat detection task where participants counted their heartbeats during different time intervals. Interoceptive awareness was assessed by the Multidimensional Assessment of Interoceptive Awareness (MAIA). The “passability ratio” (the aperture size for a 50% positive response rate, divided by shoulder width), assessed by the body-scaled action-anticipation task, was higher for fibromyalgia participants, indicating disrupted exteroceptive awareness. Overestimating body size correlated positively with pain and its impact on functionality, but not with pain intensity. There was no difference in IS between groups. Fibromyalgia patients exhibited a higher tendency to note bodily sensations and decreased body confidence. In addition, the passability ratio and IS score correlated negatively across the whole sample, suggesting an inverse relationship between exteroceptive and interoceptive body awareness. There was a lower tendency to actively listen to the body for insight, with higher passability ratios across the whole sample. Based on our results and building on the fear-avoidance model, we outline a proposal that highlights possible interactions between exteroceptive and interoceptive body awareness and pain. Movement based contemplative practices that target sensory-motor integration and foster non-judgmental reconnection with bodily sensations are suggested to improve body confidence, functionality, and quality of life.